Identification of Fungal Communities Associated with the Biodeterioration of Waterlogged Archeological Wood in a Han Dynasty Tomb in China - Liu, Zijun; Wang, Yu; Pan, Xiaoxuan; Ge, Qinya; Ma, Qinglin; Li, Qiang; Fu, Tongtong; Hu, Cuiting; Zhu, Xudong; Pan, Jiao (Frontiers in Microbiology, 2017)
The Mausoleum of the Dingtao King (termed ‘M2’) is a large-scale huangchang ticou tomb that dates to the Western Han Dynasty (206 B.C.–25 A.D.). It is the highest-ranking Han Dynasty tomb discovered to date. However, biodeterioration on the surface of the tomb M2 is causing severe damage to its wooden materials. The aim of the present study was to give insight into the fungal communities colonized the wooden tomb. For this purpose, seven samples were collected from different sections of the tomb M2 which exhibited obvious biodeterioration in the form of white spots. Microbial structures associated with the white spots were observed with scanning electron microscopy. Fungal community structures were assessed for seven samples via a combination of high-throughput sequencing and culture-dependent techniques. Sequencing analyses identified 114 total genera that belonged to five fungal phyla. Hypochnicium was the most abundant genus across all samples and accounted for 98.61% to 99.45% of the total community composition. Further, Hypochnicium sp. and Mortierella sp. cultures were successfully isolated from the tomb samples, and were distinguished as Hypochnicium sp. WY-DT1 and Mortierella sp. NK-DT1, respectively. Cultivation-dependent experiments indicated that the dominant member, Hypochnicium sp. WY-DT1, could grow at low temperatures and significantly degraded cellulose and lignin. Thus, our results taken together suggest that this fungal strain must be regarded as a serious threat to the preservation of the wooden tomb M2. The results reported here are useful for informing future contamination mitigation efforts for the tomb M2 as well as other similar cultural artefacts.